Stanhopeinae Mesoamericanae, V. El aroma floral de las Stanhopeas de Mexico - Gerlach, Günter (2013)
Analyses of the floral fragrances of 12 of the 13 species of Stanhopea from México are presented here. Some of the species, such as S. hernandezii, S. martiana, S. tigrina, S. intermedia and S. graveolens are well characterized by their floral fragrances, while the other two species S. ruckeri and S. intermedia have two chemotypes. Furthermore, there exist two groups of 3 species each which are not delimited by their floral fragrances, just as their taxonomy and morphology also are not easily described and clear.